The simulations of transients in a shell transformer with movable magnetic shunt - Tomczuk, Bronisław; Wajnert, Dawid; Weber, Dawid (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
This paper proposes a hybrid field-circuit model of a single-phase shell-type transformer that incorporates a three-dimensional analysis of the magnetic field in a transformer with beveled edges of the magnetic shunt. The finite element method (FEM) was employed, and the expressions for computing the differential and integral parameters of the magnetic field were provided. For various positions of the magnetic shunt, the self- and mutual inductances of the transformer windings were calculated. Their values were stored in matrix form, serving as input data for the transformer circuit model. The differential equations governing the operation of a transformer with a movable magnetic shunt were formulated using Lagrangian methods and applied to the T-type equivalent circuit of the transformer. This simulation model was experimentally validated, with measured and simulated time-course currents showing close agreement. Furthermore, three electric arc models were incorporated to assess the proposed method under nonlinear loading. The results show that the suggested mathematical model accurately predicts the transformer transients across diverse operating scenarios. Moreover, the presented simulation offers potential for broader application to other electromagnetic objects.